Transformation of Household Credit Behavior in the Conditions of Digitalization of the Financial Services Market - Dubyna, M; Zhavoronok, A; Kudlaieva, N; Lopashchuk, I (Journal of Optimization in Industrial Engineering, 2021)
Within the article, the impact of modern digitalization processes on changing household credit behavior is considered. Much attention is paid to defining the essence of digitalization and exploring the features of its impact on the financial services market. Accordingly, the content of household credit behavior and its individual models are examined. This behavior is proposed to be considered as a process of interaction between entities engaged in joint business activities with financial institutions regarding the receipt of temporary financial resources from banking and non-banking institutions with subsequent use to meet their own needs on terms of return, payment, expediency and security. Within the article, basic features that are inherent in both the classic model of obtaining credit services by clients of financial institutions and the new model of lending, which is formed today as a result of the impact of digitalization processes, are defined and systematized. Study of the results of the analysis of current trends in the development of the financial services market made it possible to identify main perspective directions for further transformation of credit household behavior, the process of lending and changing the paradigm of lending to financial institutions.
Keywords: Digitalization, Financial Services Market, Financial Behavior, Credit Behavior, Financial Institution.